Faktor yang Berhubungan dengan Keberadaan Cemaran Timbal pada Gorengan Ote-Ote di Kota Surabaya Tahun 2022 - Marcellina Tania Ratanika; Trias Mahmudiono (Universitas Airlangga, 2023)
Background: Lead (Pb) is a chemical contamination commonly found in fritters street food snacks. Ote-ote is one of them. Objectives: This study researched factors associated with Lead (Pb) contamination in ote-ote fritters in Surabaya. Methods: This research was an analytical observational using a cross sectional method. The number of samples was 38 traders who fulfilled the inclusion and exclusion criteria that chosen with random sampling technique. Samples were qualitatively analyzed with Lead (Pb) Easy Kit and chi-square statistic test. Results: The result showed that most of ote-ote in Surabaya contained Lead (Pb) with factors associated were monthly income and sanitary facilities. In addition, Lead (Pb) was commonly found in food carts, high school education, and low level of knowledge. Conclusions: Factors associated with Lead contamination in Ote-Ote fritters were trader's monthly income and facilites sanitary. Stakeholder collaboration, such as BPOM, Dinas Kesehatan, and trader's awareness are needed to prevent Lead contamination in ote-ote.